Applications des picable motive in some contemporary crimes - عبد الله فراس عبد المنعم; ابراهيم رسل خالد (Journal of Legal Sciences, 2019)
Considered despicable motive of the most accurate indicators that reveal the amount of serious criminal, Which involves the character of the perpetrator and on whose basis the penalty is estimated,The origin is that the despicable motive doesnot affect the existence of the crime ,But it affects in punishment, the despicable motive has a set of characteristics that ensure its distinctiveness from other cases that have an indication of the perpetrator of the crime,the despicable motive has privacy in some contemporary crimes, as it enters the composition of the criminal intent of the actor does not do the moral side without it.and therefore it is not doing crime,Such as terrorist offenses, hate crimes and the offense of incitement to hatred,The motive for terrorist crimes is to spread fear and terror in society to achieve a terrorist objective,It is an ideology that the terrorist wants to deploy and apply coercively to all.The terrorist motive is aimed at changing the social structure and the pattern of social relations,It takes the attack an interest of great importance that exceeds the importance of public interest,It deserves to be described as a supreme social interest,The perpetrator of hate crimes, the instigator of hatred, attacks the interest of society in maintaining social peace,The gravity of the motive for the incitement of hatred, He is the instigator of spreading hatred, Lies in that it drives the instincts primitive and the most dangerous instinct of aggression,The interest of society in preserving its cohesion and unity,They tear apart the social fabric among the members of society.